2012
DOI: 10.1097/mpg.0b013e3182369dc8
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Evaluation and Satisfaction With Autologous Bowel Reconstruction in Children With Short Bowel Syndrome

Abstract: The present study found that AGIR improved the physical well-being of the child and gave the impression of improvements on specific QoL aspects for both the child and the parents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…At any rate, a close association has been found between the disease suffered by the patient and its impact on everyday life issues (Wogelius et al, 2011;Varni et al, 2012). Other studies have suggested that the satisfaction of the patient's family is linked to a significant improvement in their capacity to adapt to the patient's situation (Pasquarella et al, 2007;Edge et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…At any rate, a close association has been found between the disease suffered by the patient and its impact on everyday life issues (Wogelius et al, 2011;Varni et al, 2012). Other studies have suggested that the satisfaction of the patient's family is linked to a significant improvement in their capacity to adapt to the patient's situation (Pasquarella et al, 2007;Edge et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…25 In a retrospective study recording parent's opinions on their child's bowel function before and after autologous intestinal reconstruction surgery, bowel habits were found to improve postoperatively, however, stooling frequency or consistency were not defined and preoperative bowel function was based on descriptions made after surgery. 64 One study addressing the influence of an enterostomy found that parents of infants with a stoma reported their children slept better and cried less compared to other infants. On the other hand, adolescents with an enterostomy had more negative thoughts about their health than those without a stoma.…”
Section: Summary Of Available Studies Among Children With Intestinal mentioning
confidence: 99%
“…58,59 Tendency towards delayed psychomotor skills also emerged in parent interviews: 40% of IF toddlers were reported to have difficulties in achieving normal developmental milestones, 25 and parents rated the overall developmental progress of children undergoing autologous intestinal reconstruction surgery as "poor". 64 Only one study including only nine IF patients, who had all weaned off PN, reported normal motor skills at median age of five years. 60…”
Section: Psychomotor Outcomesmentioning
confidence: 99%
“…9 Other authors studied the quality of life of parents of children on home PN and described a significant deterioration for either social life, family life, sex life, or work in comparison with controls. 10 Our team previously analyzed caregivers' perception of the effect of autologous gastrointestinal reconstruction (AGIR) on the lives of their child with SBS and themselves, 11 using a modified version of O'Neill et al 12 questionnaire. The study concluded that AGIR improved the physical wellbeing of the children.…”
Section: Introductionmentioning
confidence: 99%
“…It was easier for the caregivers to take care of their children, with less frustration; they were able to enjoy their children more and to spend more quality time with them. 11 This study aimed to provide a more comprehensive evaluation of quality of life and family impact in patients with SBS, who either received AGIR or not, using the Pediatric Quality of Life Inventory (PedsQL) measurement model. In pediatric chronic health conditions, like SBS, the impact of disease and treatment on family functioning is a salient concern given the essential role of the family in child adaptation to disease.…”
Section: Introductionmentioning
confidence: 99%